Bacteriological quality of sliced fruits sold at road site in Maiduguri, Borno State - Allamin, IA; Borkoma, MB; Abbas, M Ibu; Wazin, MA (International Journal of Environment, 2015)
The study was conducted to assess the bacteriological quality of sliced fruits, Fresh cut fruits collected from different stationary vendors in Maiduguri metropolis and were analysed to determine their bacteriological quality. All samples examined were contaminated with bacteria load. The Total aerobic plate count (TAPC) range from 1.8x105 – 3.4x105 for pawpaw, 1.9x105- 6.8x105 for pineapple and 1.5x105- 5.1x105 for watermelon, Likewise Total coliforms count range from 1.0x104 – 2.0x104 for pawpaw, 1.0x104- 3.8x104 for pineapple and 1.0x105- 4.6x104 for watermelon. The bacterial isolate were identified as Staphylococcus aureus, E.coli, Pseudomonas, Shigella sp. and Salmonella sp. The results obtained shows that sliced fruits sold in Maiduguri metropolis are habited by pathogenic bacteria. Therefore educating our fruit vendors on food hygiene, adequate packaging/covering of fruits on display for sale and washing of fruits before consumption is recommended. DOI: http://dx.doi.org/10.3126/ije.v4i2.12645 International Journal of Environment Vol.4(2) 2015: 236-242